Advancement of STEM-Based E-Student Worksheet To Enhance The HOTS of Elementary School Students - Zainil, Melva; Kenedi, Ary Kiswanto; Asnawi (Universitas Pendidikan Ganesha, 2022)
During the covid-19 pandemic, there was a demand for online learning innovations that could meet the characteristics of elementary school students and develop HOTS for elementary school students. The goal of this study is to develop a STEM-based E-Student Worksheet to enhance valid and effective HOTS of elementary school students during the COVID-19 pandemic. HOTS measured in this study was the cognitive level C4, C5 and C6.This study used a four-dimensional model to conduct development research. The participants in this study were elementary school students in second grade as many as 60 students. The qualitative and quantitative data used in this study included observation sheets, documentation, questionnaires, and test questions. Qualitative data was analysed by collecting data, reducing data, and drawing conclusions, whereas quantitative data was analysed by applying the independent t-test. According to the study's findings, a STEM-based E-Student Worksheet had been developed to enhance elementary school students' valid and effective HOTS during the covid-19 pandemic. The findings of this study can be used by teachers to guide them through the online learning process during the COVID-19 pandemic.